Estabilidade de compostos bioativos em polpa congelada de amora-preta (Rubus fruticosus) cv.Tupy - Jacques, Andressa Carolina (2009)
Brazil is considered one of the major consumer´s country of fruits, occupying the third worldwide position. The diversity of fruit for the market is growing, but their properties and activities are not fully determined. However, from the beginning of the 90s, a large fruit supply is justifying studies related to the development of new products, which in most cases concentrates the major consumption form as raw fruit or pulp. This work aimed to produce pulp from blackberry cv. Tupy, and store it under different temperature conditions (-10, -18 and -80 ºC) for 6 months, evaluating the stability of its main phytochemicals after processing and during the storage period. The results showed that the temperature of -10 °C was not sufficient to cause significant changes in relation to total phenols, total anthocyanins, antioxidant capacity and titrable acidity (2 months). The temperature of -18 ° C was not sufficient to cause significant changes in the pulp with respect to: total phenols and antioxidant capacity (4 months), total anthocyanins (2 months) and β-carotene (6 months). At temperature of -80 ° C, few changes were caused in the pulp stored for 6 months, and observed only small changes in soluble solids, hydroxybenzoic acid. Total and individual carotenoids in any of the three IPF temperatures sufficient to avoid losses. In Tocopherol, only in the pulp stored at -80 ° C for 2 months there was no change.The ascorbic acid was completely degraded within 6 months of storage at all temperatures (-10, -18 and -80 °C). The phenolics were the compounds that most contributed to the antioxidant capacity of blackberry cv. Tupy.